Meta-analysis shows similar re-bleeding rates among Western and Eastern populations after index video capsule endoscopy. Issue 3 (March 2018) - Tziatzios, Georgios; Gkolfakis, Paraskevas; Hassan, Cesare; Toth, Ervin; Zullo, Angelo; Koulaouzidis, Anastasios; Dimitriadis, George D.; Triantafyllou, Konstantinos
Abstract: Background & aims: Video capsule endoscopy (VCE) is the first-line diagnostic procedure for investigating obscure gastrointestinal bleeding (OGIB). Different re-bleeding rates following index VCE have been reported among Western and Eastern studies. Methods: We conducted a comprehensive literature search to identify studies examining re-bleeding rates after VCE for OGIB. Meta-analysis assessed the pooled proportion of re-bleeding events after VCE for OGIB according to study's origin (Western vs. Eastern) and according to the length of follow-up (≥24 months vs. <24 months). We also calculated the re-bleeding odds ratios (OR; 95% CI) after positive vs. negative index VCE, overt vs. occult initial presentation of bleeding and after interventional treatment for positive index cases, according to the study's origin. Results: We included 46 (30 Western and 16 Eastern) studies with 5796 patients. Significant heterogeneity was detected among meta-analyzed studies. Overall, the pooled re-bleeding rate was similar between Western (29%; 95% CI: 23–34) and Eastern (21%; 95% CI: 15–27) populations, irrespective of the length of follow-up. The odds of re-bleeding was significantly higher after positive as compared to negative index VCE in Eastern studies (OR: 1.77; 95% CI: 1.07–2.94). Application of specific treatment after positive index VCE was associated with lower re-bleeding odds in both Western (OR: 0.37; 95% CI: 0.16–0.87) and Eastern (OR: 0.39; 95% CI: 0.21–0.72) populations. Conclusions: Patients undergoing VCE for OGIB have similar re-bleeding rates in the East and the West, regardless of the length of follow-up. However, increased re-bleeding odds after positive index VCE is observed in Eastern studies.